256‐MDCT for evaluation of urolithiasis: Iterative reconstruction allows for a significant reduction of the applied radiation dose while maintaining high subjective and objective image quality. Issue 3 (3rd March 2014) - Veldhoen, Simon; Laqmani, Azien; Derlin, Thorsten; Karul, Murat; Hammerle, Diego; Buhk, Jan‐Hendrik; Sehner, Susanne; Nagel, Hans D.; Chun, Felix; Adam, Gerhard; Regier, Marc
Abstract Purpose Multidetector CT (MDCT) is the established imaging modality in diagnostics of urolithiasis. The aim of iterative reconstruction (IR) is to allow for a radiation dose reduction while maintaining high image quality. This study evaluates its performance in MDCT for assessment of urolithiasis. Materials and Methods Fifty‐two patients underwent non‐contrast abdominal MDCT. Twenty‐six patients were referred to MDCT under suspicion of urolithiasis, and examined using a dose‐reduced scan protocol (RDCT). Twenty‐six patients, who had undergone standard‐dose MDCT, served as reference for radiation dose comparison. RDCT images were reconstructed using an IR system (iDose4™, Philips Healthcare, Cleveland, OH, USA). Objective image noise (OIN) was recorded and five radiologists rated the subjective image quality independently. Radiation parameters were derived from the scan protocols. Results The CTDIvol could be reduced by 50% to 5.8 mGy (P < 0.0001). The same reduction was achieved for DLP and effective dose to 253 ± 27 mGy*cm (P < 0.0001) and 3.9 ± 0.4 mSv (P < 0.0001). IR led to a reduction of the OIN of up to 61% compared with classic filtered back projection (FBP) (P < 0.0001). The OIN declined with increasing IR levels. RDCT with FBP showed the lowest scores of subjective image quality (2.32 ± 0.04). Mean scores improved with increasing IR levels. iDose6 was rated with the best mean score (3.66 ± 0.04). Conclusion The evaluated IR‐tool and protocol may be applied to achieve a considerable radiation dose reduction in MDCT for diagnostics of urolithiasis while maintaining a confident image quality. Best image quality, suitable for evaluation of the entire abdomen concerning differential diagnoses, was achieved with iDose6.